HUBUNGAN PEMBIASAAN (TA’WĪD) BERBASIS NILAI-NILAI ISLAM DENGAN KEDISIPLINAN BELAJAR SISWA DI MIN 2 KARAWANG - Yani Yani; Vina Febiani Musyadad; Rahman Tanjung (Prodi PGMI STAI Sabili Bandung, 2026)
This study was motivated by the importance of students’ learning discipline at the madrasah ibtidaiyah level and the need for a structured habituation strategy to develop orderly, responsible, and consistent learning behavior. This study aimed to describe an Islamic values-based habituation strategy, describe students’ learning discipline, and analyze the relationship between both variables among fifth-grade students at MIN 2 Karawang. This study employed a quantitative approach with a correlational design. The sample consisted of 52 fifth-grade students selected through total sampling. Data were collected through questionnaires, observation, and documentation, and then analyzed using descriptive statistics, normality testing, and Spearman Rank correlation. The results showed that the Islamic values-based habituation strategy was in the high category with a mean score of 30.79, while students’ learning discipline was also in the high category with a mean score of 31.71. The highest indicator of the habituation strategy was behavioral reinforcement, while the highest indicator of learning discipline was responsibility. The correlation test revealed a positive, significant, and strong relationship between the Islamic values-based habituation strategy and students’ learning discipline, with a correlation coefficient of 0.774 and a significance value of less than 0.001. In conclusion, the better the Islamic values-based habituation strategy is implemented, the higher the students’ learning discipline will be.